Cover Feature: Atomically Defined Monocarborane Copper(I) Acetylides with Structural and Luminescence Properties Tuned by Ligand Sterics (Chem. Eur. J. 37/2019). Issue 37 (21st May 2019) - Zhang, Kang; Shen, Yunjun; Yang, Xiaoli; Liu, Jiyong; Jiang, Tao; Finney, Nathaniel; Spingler, Bernhard; Duttwyler, Simon
Abstract : The monocarborane cluster is used as a building block for the preparation of luminescent copper(I) complexes. Treatment of the 12‐alkynyl‐substituted cage with CuI and ammonia affords an isolable polymeric intermediate. Addition of phosphine and pyridine ligands transforms this intermediate to products featuring two to ten Cu centers. In the solid state, the products exhibit phosphorescence across the visible spectrum in colors from blue to deep red. The picture shows how the starting materials are transformed into copper complexes stabilized by N and P ligands. More information can be found in the Full Paper by N. Finney, B. Spingler, S. Duttwyler et al. on page 8754 .